Strengthening Character Education Through The Jumpa Berlian Program For State Elementary School Students In Posigadan District, South Bolaang Mongondow Regency - Lin Eka Putri Usman; Zulaecha Ngiu; Sukarman Kamuli (Cita konsultindo, 2025)
This research aims to describe and analyse the strengthening of character education through the Jumpa Berlian (Jumat Pagi Bersih-Bersih Lingkungan/Friday Morning Environmental Clean-up) program among state elementary school students in Posigadan Sub-district, Bolaang Mongondow Selatan Regency. The program serves as a strategic effort to instill character values through environmentally-based activities conducted regularly and participatively. A qualitative approach with a multiple case study design was employed, focusing on three schools: SDN Momalia 3. SDN Pilolahunga, and SDN Luwoo. Data were collected through in-depth interviews, participatory observation, and documentation, with data triangulation used to verify the validity of findings. The results showed that the Jumpa Berlian program significantly contributes to instilling character values such as democracy, nationalism, love of peace, cooperation, patriotism, and environmental awareness. The program's success is supported by factors such as the principal's commitment, teacher collaboration, and a school culture that promotes habituation of character values. However, challenges remain, including limited cleaning equipment, uneven student participation, and time constraints. Adaptive strategies implemented by schools, such as activity innovations, student role rotations, and reward systems, have helped maintain program sustainability and effectiveness in character development. These findings reinforce the relevance of the ecological citizenship theory as a conceptual foundation for environmentally based character education.